Nanotribology and nanomechanics II Nanotribology, biomimetics, and industrial applications - Bhushan, Bharat 1949- (Springer, 2011)
The comprehensive reference and textbook serves as a timely, practical introduction to the principles of nanotribology and. Assuming some familiarity with macroscopic tribology, the book comprises chapters by internationally recognized experts, who integrate knowledge of the field from the mechanics and materials-science perspectives. They cover key measurement techniques, their applications, and theoretical modelling of interfaces, each beginning their contributions with macro- and progressing to microconcepts.